Metal recovery in nickel smelting and converting operations - Grimsey, Eric (The Minerals, Metals and Materials Society, 1993)
Nickel smelting and converting can be viewed as processes in which iron is either partitioned or transported between matte and slag. Metal recovery depends on the mass of iron transported to slag, the thermodynamic environment in which the transport is made, and the extent to which the slag, once formed, is left in contact with the matte. The importance of these effects is discussed with reference to a new equation which describes metal recovery in terms of a mass balance and a thermodynamically related parameter which is easily measured in practice.